2016
DOI: 10.1002/2016ja023270
|View full text |Cite
|
Sign up to set email alerts
|

Proton cyclotron waves occurrence rate upstream from Mars observed by MAVEN: Associated variability of the Martian upper atmosphere

Abstract: Measurements provided by the Magnetometer and the Extreme Ultraviolet Monitor (EUVM) on board the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft together with atomic H exospheric densities derived from numerical simulations are studied for the time interval from October 2014 up to March 2016. We determine the proton cyclotron waves (PCWs) occurrence rate observed upstream from Mars at different times. We also study the relationship with temporal variabilities of the high‐altitude Martian hydrogen ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
106
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 68 publications
(134 citation statements)
references
References 53 publications
18
106
0
Order By: Relevance
“…In any case, SWIA observations indicate a remarkable level of seasonal variability in the exosphere, implying an order of magnitude variation in the column density that interacts with the solar wind outside of the bow shock during the time period surveyed. Other MAVEN observations of UV emission from the hydrogen corona, low‐frequency waves seen upstream near the proton cyclotron frequency [ Romanelli et al ., ], and pickup ions [ Rahmati et al ., ] confirm a seasonal variation in the corona during the MAVEN mission. This variation closely tracks the EUV flux, which primarily varies with heliocentric distance over this time period (solar cycle effects may play a secondary role).…”
Section: Solar Energy Inputs To the Martian Systemmentioning
confidence: 62%
“…In any case, SWIA observations indicate a remarkable level of seasonal variability in the exosphere, implying an order of magnitude variation in the column density that interacts with the solar wind outside of the bow shock during the time period surveyed. Other MAVEN observations of UV emission from the hydrogen corona, low‐frequency waves seen upstream near the proton cyclotron frequency [ Romanelli et al ., ], and pickup ions [ Rahmati et al ., ] confirm a seasonal variation in the corona during the MAVEN mission. This variation closely tracks the EUV flux, which primarily varies with heliocentric distance over this time period (solar cycle effects may play a secondary role).…”
Section: Solar Energy Inputs To the Martian Systemmentioning
confidence: 62%
“…Yamauchi et al () found that pickup ions upstream from Mars are significantly enhanced around perihelion and suggested this was due to a seasonal enhancement in the underlying neutral exosphere. Romanelli et al () confirmed such a seasonal variation in the neutral exosphere, with neutral hydrogen densities (at altitides of 3 Mars Radii) at perihelion ≈4× denser than at aphelion. Romanelli et al () discovered that this coincided with a significant enhancement in the abundance of the ULF ("proton cyclotron") waves discussed in this study.…”
Section: A Search For More Eventsmentioning
confidence: 88%
“…The intensity of ULF waves upstream of Mars (Halekas et al, ) and Venus (Delva et al, ) is strongly dependent upon the orientation of the interplanetary magnetic field, with more intense waves being observed when the IMF is radial , for example, parallel to the Sun‐Planet line. At Mars, ULF waves exhibit a strong seasonal variation, with stronger waves closer to perihelion (Romanelli et al, ) due to the exospheric hydrogen that gets heated and enhanced at higher altitudes due to the brightening sunlight (Yamauchi et al, ). These waves attempt to propagate upstream (sunwards) but are blown backward toward the bow shock by the solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of spectral indices with small positive values for L s ∼0 and L s ∼90 (see Figures b and c) indicates that this energy injection mechanism is not dominant for these latter time intervals. An investigation of proton cyclotron wave occurrence rate by Romanelli et al [], encompassing these same three time periods, revealed a high occurrence rate of proton cyclotron waves at L s ∼270 and a drastic diminishment at L s ∼0 and L s ∼90. Thus, we infer that the small positive values of spectral indices reveal the presence of proton cyclotron waves.…”
Section: Discussionmentioning
confidence: 99%